Factors Associated with Successful Vaginal Birth After a Primary Cesarean Section in Women with an Optimal Inter-Delivery Interval - Maroyi R; Naomi B; Moureau MK; Marceline BS; Ingersoll C; Nerville R; Mukwege D (Dove Medical Press, 2021)
Raha Maroyi,1,2 Bahaya Naomi,2 Madeline K Moureau,3 Balungwe Sifa Marceline,1 Celeste Ingersoll,4 Roselyn Nerville,5 Denis Mukwege1,2,6 1Department of Obstetrics and Gynecology, Panzi Referral Hospital, Bukavu, South Kivu, Democratic Republic of Congo; 2Université Evangélique en Afrique (UEA), Bukavu, South Kivu, Democratic Republic of Congo; 3Department of Obstetrics and Gynecology, University of Wisconsin School of Medicine and Public Health, Madison, WI, USA; 4Department of Statistics, Brigham Young University, Provo, UT, USA; 5University of Utah School of Medicine, Salt Lake City, UT, USA; 6International Center for Advanced Research and Training (ICART), Bukavu, South Kivu, Democratic Republic of CongoCorrespondence: Raha MaroyiUniversité Evangélique en Afrique (UEA), PO Box: 266, Bukavu, South Kivu, Democratic Republic of CongoTel +243 997 254 812Email ken.raha01@gmail.comPurpose: We sought to determine the success rate of VBAC and factors associated with achieving VBAC at a referral hospital in the Democratic Republic of Congo in women with a subsequent pregnancy greater than or equal to 18 months from their primary cesarean section (CS).Patients and Methods: Patients were included for participation if they had an inter-delivery interval (IDI) of at least 18 months from their primary CS, accepted TOLAC, and had no contraindications. Information was collected about patients' demographics, obstetric history, and factors impacting their labor process. Descriptive analyses compared patients that had a successful VBAC and those who did not. Univariate and multivariate binary logistic regression models identified factors associated with a successful VBAC.Results: Among 231 eligible patients who attempted a VBAC, 57.6% (133) achieved VBAC. Participants had a mean age of 29 (SD 6), with the majority having a prior vaginal delivery (68.8%). VBAC was positively associated with a higher Bishop score (AOR 1.12, 95% CI 1.02, 1.23) and a spontaneous labor onset (AOR 3.06, 95% CI 1.52, 6.17). VBAC was negatively associated with a macrosomic fetus (AOR 0.21, 95% CI 0.08, 0.58).Conclusion: TOLAC results in VBAC more than half the time and is associated with a spontaneous labor onset and a higher Bishop score. Women with a macrosomic fetus were more likely to have an unsuccessful VBAC, resulting in an RCS. An optimal IDI was not enough to ensure a successful VBAC. Upon patients' arrival to the hospital, practitioners should re-evaluate their eligibility to attempt a VBAC based on their Bishop score and if they had a spontaneous labor onset to decrease the health risks of an RCS.Keywords: trial of labor, delivery, repeat cesarean section, sub-Saharan Africa, Democratic Republic of Congo